Understanding the photoelectrochemical properties of a reduced graphene oxide–WO3 heterojunction photoanode for efficient solar-light-driven overall water splitting - Lin, Jingdong (2013)
WO3–reduced graphene oxide (WO3–RGO) heterojunction electrodes were prepared for photoelectrochemical (PEC) overall water splitting. The WO3 photoanode incorporated with RGO showed significantly enhanced PEC properties and, hence, photocatalytic water splitting, compared to the bare WO3 at a bias larger than 0.7 V vs. Ag/AgCl, while a decrease in the PEC properties of WO3–RGO compared to the WO3 electrode was observed at a bias smaller than 0.7 V vs. Ag/AgCl. RGO could play a favorable role in enhancing the electron–hole separation due to the presence of interface states according to the Bardeen model, but it could also provide active sites for the electron–hole recombination. A more positive applied bias is in favor of effective electron–hole separation, by means of quick collection and transport of electrons by RGO. As a result, a higher PEC performance of WO3–RGO can only be realised at a relatively more positive bias. This study gives insights into the complex nature of a RGO–semiconductor heterojunction, and its implications on the overall photoconversion efficiency.